The use of hierarchical scheduling in the ingress edge router of a DiffServ domain / Husna Zainol Abidin, Norashidah Md. Din and Norsheila Fisal - Zainol Abidin, Husna; Md. Din, Norashidah; Fisal, Norseila (UiTM Press, 2010)
Scheduling mechanisms ensure that different type of traffics obtain their share of resources such as link bandwidth and ensure that any spare capacity is distributed fairly. In other words it can be said that scheduler is responsible in reordering the output queue. To enhance the Quality of Service (QoS) granularity in a Differentiated Services (DiffServ) QoS model, DiffServ should be facilitated with a scheduler rather than normal First In First Out (FIFO) mechanism such as Priority Queueing, Round Robin, Weighted Round Robin, Fair Queueing and many more. However, these types of schedulers have their own setbacks, thus this paper analyzes and enhances the performance of DiffServ network by deploying a hierarchical scheduling technique in the DiffServ ingress edge router.